The walking dead. Fall of the Governor [compact disc, unabridged] part two - Kirkman, Robert (Kirkman, Robert. Walking dead, 2014)
In Rise of the Governor, uber-villain Philip Blake journeyed from his humble beginnings directly into the dark heart of the zombie apocalypse, and became the self-proclaimed leader of a small town called Woodbury. In Book Two, The Road to Woodbury, an innocent traveler named Lilly Caul wound up in the terrifying thrall of Phillip Blake's twisted, violent dictatorship within Woodbury's ever tightening barricades.